Leadership and Negotiation Skills in Finance - Fall, Ibrahima (Digital Repository of Theses - SSBM Geneva, 2025)
The thesis highlights the integral relationship between leadership and negotiation. These two functions are not mutually exclusive but rather complementary and mutually reinforcing. Leadership skills are essential to any negotiation, because successful outcomes happen more often when you can create a win-win situation for both parties. Having a strong leadership skills provides a foundation for successful negotiation by establishing trust, fostering open communication, and creating a shared vision. Leaders who possess qualities such as empathy, active listening, and emotional intelligence.In reality, good leadership almost always involves negotiation, and good leaders are invariably effective negotiators. Recognizing the interconnectedness of leadership and negotiation is crucial for developing professionals who can navigate complex challenges and achieve optimal results. By cultivating both leadership qualities and negotiation skills, individuals can become more effective in their roles, whether they are leading teams, managing projects, or representing their organizations in negotiations. As a Tool for Leadership, the Negotiation skills are essential for leaders to effectively influence and guide their teams and organizations. By engaging in collaborative negotiation, leaders can build consensus, resolve conflicts, and motivate individuals to work towards common goals. Negotiation can also be a powerful tool for leaders to gather information, build relationships, and gain buy-in for new initiatives. Resource allocation is a core responsibility of financial leaders. It involves determining how the organization's financial resources will be used to achieve its strategic goals. This process is inherently a negotiation, both internally and externally When the organization has a Deal Making, a Negotiation-Intensive Domain is activated and financial leaders are frequently involved in complex transactions that require skillful negotiation. These deals can significantly impact the organization's financial health, growth, and long-term strategy. On the Stakeholder Management when the organization Navigating Diverse Interests, Financial leaders operate within a complex web of relationships, each stakeholder having distinct interests and expectations. Effective stakeholder management requires understanding these diverse perspectives and negotiating mutually acceptable outcomes. Another aspect is essential to get the two both skills: the conflict resolution where the financial leaders have to disputes conflict related to financial and social matters. Conflict Resolution is a vital skill for financial leaders, and it's heavily reliant on negotiation. The research will address several key themes and research questions, including: • How do different leadership styles (e.g., transformational, transactional, laissez-faire) influence negotiation behaviors and outcomes? • What are the specific negotiation skills and tactics that are most effective for leaders in various contexts? • How does the use of power and influence impact the interplay between leadership and negotiation? • What are the ethical considerations involved in the intersection of leadership and negotiation? • How can organizations develop leaders who are both effective negotiators and inspiring leaders? The method used for the research is the qualitative research which is considered to be the approach where researchers are interested in building based on people's experience and not in obtaining information that can be generalized to other larger groups. This approach consist on interviews in the organization and collect the data they collected from the interviews. This involves moving from the specific to the general and qualitative researchers do not base their research on predetermined assumptions. It allows for greater flexibility than in quantitative research. Also the literature review will utilize a systematic approach to identify, select, and analyze relevant research. This will involve searching electronic databases such as JSTOR, Google Scholar, and EBSCOhost using keywords related to leadership, negotiation, and their intersection. The review also focus on peer-reviewed journal articles, books, and conference proceedings published in recent years.